Evaluation of interferon-stimulated genes in peripheral blood granulocytes as sensitive responders to bovine early conceptus signals. (November 2017) - Toji, N.; Shigeno, S.; Kizaki, K.; Koshi, K.; Matsuda, H.; Hashiyada, Y.; Imai, K.; Takahashi, T.; Ishiguro-Oonuma, T.; Hashizume, K.
Highlights: Expression of interferon receptors was higher in peripheral blood granulocytes than in mononuclear cells. Changes in global gene expression were observed in granulocytes treated with recombinant interferon-tau (IFNT). Interferon-stimulated genes were also highly expressed in recombinant IFNT-treated granulocytes. Granulocytes specifically responded to IFNT and its gene expression is a suitable tool to determine pregnancy status. Abstract: Early detection of gestation is important in the bovine industry. New methods have been developed to detect gene expression in leucocytes induced by interferon-tau (IFNT) as gestation biomarkers. However, it is debatable which blood cell is suitable for detecting gene expression. This study was aimed at confirming whether granulocytes respond to IFNT specifically. Granulocytes and mononuclear cells (MNCs) from cows, and several types of bovine cultured cells, were treated with recombinant (r) IFNT and gene expression was analysed by quantitative real-time reverse transcriptase (RT)-PCR and microarray analysis. Expression levels of IFN receptors (R1 and R2) were approximately 30- to 900-fold higher in granulocytes than in other cultured cells, and 1.5- to 2.5-fold higher in MNCs than in granulocytes. Microarray analysis following a 2 h recombinant IFNT (rIFNT) treatment revealed expression changes for 900 genes in granulocytes. Genes with expression changes included known IFN-stimulated genes (ISGs; ISG15, OAS1, MX1, and MX2 ). Eighteen genes were selected following granulocyte microarray analysis and their expression changes were confirmed in early gestation, which revealed that nine genes had significantly higher expression levels in pregnant than in non-pregnant animals. In conclusion, granulocytes specifically responded to rIFNT treatment and the resulting gene expression changes correlated with those in vivo. Microarray analysis indicated that various genes showed expression changes in rIFNT-treated granulocytes, which may result in the identification of alternate candidate genes for the early detection of gestation. These results strongly indicate that gene expression in granulocytes is a suitable tool to determine pregnancy status.